Estudo químico e farmacológico de Senna reticulata Willd. (sin. Cassia reticulata Willd.) - Santos, Rogério Nunes dos (2007)
This work decrib the phytochemical investigations of Senna reticulata Willd., (Leguminoseae), popularly known as “mangerioba grande” in the Brazilian Northeastern. Medicinal plant used for of liver illnesses, for rheumatism and menstrual pains. The genera Senna, Chamaecrista and Cassia were investigated from to from your compounds anthraquinones told in the literature until the current days, in the interest of tracing a profile, that contributed with chemical distinction of the same ones that to some years they were confused due your great botanical similarities. The chemical studies of ethanol extract of leaves, trunk and trunk bark of S. reticulata, making possible the isolation and identification of six anthraquinones, one flavone and one bianthrone, a mixture of two triterpenes and two a mixture of glucosilated and free β-sitosterol and stigmasterol. Another stage of the work was dedicated to the study pharmacologic of S. reticulata, that through rehearsals analyzed the antioxidant potential, the activity antiparasite, antibacterials and anticonvulsant of the extracts ethanol the leaves, trunk and trunk bark and isolated substances of the referred species. The molecular structures of compounds were elucidated by spectroscopic methods such as infrared, mass epectrometry, and nuclear magnetic resonance including special pulse sequences such as 1H, 13C-COSY (nJCH, n = 1, 2 e 3) with inverse detection and comparison with literature data.